A formaçao do professor alfabetizador leitor e seus desdobramentos na sala de aula - Rocha, Raquel da Silva (2016)
The school has been the place where the children of the popular classes have their first contact with the reading. The teacher takes the place of first stimulator reading, followed by the mother and other family members. In the initial years of primary school the literacy teacher should do the important task of teaching children the act of reading and writing, as well as stimulate and encourage a relationship with love and pleasure with the reading. For this, the teacher must have a good relationship with reading. This study aims to investigate teachers' reading practices and literacy offer a proposal that contributes to the development of the teacher / player. The research was conducted in three phases. The first phase, a questionnaire was conducted for teachers of a public school in the early years in order to analyze the reading teacher practices. To deepen the understanding of reading in school, a second phase was developed, the results of external evaluations of Portuguese Language made by the students were analyzed. The third and final phase of the research was conducted two meetings with school teachers to discuss the data from external assessments and analyze the understanding they had about reading and their work in the classroom. The analysis of the three phases of the research, signaled the need for investment in reader training of teachers, given that the majority of respondents teachers do not take time to read, in addition to performing readings that contribute little personal and professional training. The data regarding the development of readers abilities of students indicated that they have difficulties in the reconstruction of meanings of texts, especially when it comes to literary texts, only 50% of students in the 5th year of school, complete the initial years with proficiency reader required to proceed with their studies. Teachers demonstrated disregard those results, and does not understand that reading is a content to be taught. In this sense, we finalized the process of analysis and diagnosis of the difficulties of teachers and students, has submitted a proposal for training of teachers in school readers. The focus of the proposal is not the reproduction of the activities in the classroom by teachers but encourage teachers a new relationship with reading through strategies that approach the diversity of literary genres and allow reflection on the meaning of reading in their life and profession